A new simple and efficient flash algorithm for T-v specifications - Cismondi Duarte, Martín (2018)
Flash calculations have innumerable applications. Fast and robust algorithms for the (T-P) variant have spread since the early 80's, when Michelsen proposed an efficient successive-substitution algorithm for this specification, the most common and important one in practice. Specification of volume instead of pressure, along with temperature (T-v), for a fluid of known composition, can also be very important in many applications, including storage tanks, fluid mechanics and flow where phase equilibrium is important such as in oil reservoir. Some recommendations on how to solve indirectly this problem can be found in the literature, as well as a few studies proposing different formulations and sophisticated methods for minimizing the Helmholtz energy. Nevertheless, there has not been so far an efficient algorithm developed specifically for the T-v specification, that could be considered equivalent to the “Michelsen T-P flash”. In this work, we propose a new algorithm for T-v flash calculations, which is based on results from adapting the classic successive substitution method for a T-P flash, with equivalent simplicity, and therefore making it very attractive for engineering calculations, especially when speed may be important. Complementary aspects like initialization of variables and application to liquid-liquid separation are also discussed. Based on the new developed algorithm and the use of equations of state, the isochoric behaviors of different multicomponent mixtures are analyzed, including a natural gas, a synthetic gas condensate, and a CO 2 -hydrocarbon mixture, considering both vapor-liquid and liquid-liquid separations. The effect of temperature on storage tanks is illustrated based on isochores, and it is also shown how these calculations can help in the search of convenient conditions for separating the condensable fraction from a natural gas.